2013
DOI: 10.1159/000346764
|View full text |Cite
|
Sign up to set email alerts
|

Noise Levels of Neonatal High-Flow Nasal Cannula Devices - An in-vitro Study

Abstract: Background: Excessive ambient noise levels have been identified as a potential risk factor for adverse outcome in very preterm infants. Noise level measurements for continuous positive airway pressure (CPAP) devices demonstrated that these constantly exceed current recommendations. The use of high-flow nasal cannula (HFNC) as an alternative non-invasive ventilation modality has become more popular in recent years in neonatal care. Objective: To study noise levels of two HFNC devices commonly used in newborns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
2
16
2
1
Order By: Relevance
“…The short duration of sessions in our study may explain the lack of differences in comfort, as longer durations are needed for the emergence of adverse experiences such as upper airway dryness caused by the high-F IO 2 face mask, 26 intolerance to CPAP, 19 or noise with HFNC. 34 However, contrary to this result, 75% of our subjects found that HFNC was more pleasant than the other oxygen delivery techniques (CPAP and high-F IO 2 , non-rebreathing face mask). In clinical practice, Sztrymf et al 15,16 reported a remarkable tolerance of HFNC over longer use.…”
Section: Comfortcontrasting
confidence: 88%
“…The short duration of sessions in our study may explain the lack of differences in comfort, as longer durations are needed for the emergence of adverse experiences such as upper airway dryness caused by the high-F IO 2 face mask, 26 intolerance to CPAP, 19 or noise with HFNC. 34 However, contrary to this result, 75% of our subjects found that HFNC was more pleasant than the other oxygen delivery techniques (CPAP and high-F IO 2 , non-rebreathing face mask). In clinical practice, Sztrymf et al 15,16 reported a remarkable tolerance of HFNC over longer use.…”
Section: Comfortcontrasting
confidence: 88%
“…Treatment intervention did not reduce HF sound as well in the in vivo as the in vitro study likely to exclusion of respiratory modes in the in vitro study. These findings support the observation that CPAP contributes to HF sound energy in neonatal intensive care units 31 .…”
Section: Resultssupporting
confidence: 90%
“…Previous studies [28][29][30][31] supported the need to evaluate differences among modes of respiratory therapy. Surenthiran et al measured sound frequencies outside and within the ears of neonates receiving one of three respiratory therapy modes 28 .…”
Section: Ventilators Vs Cpapmentioning
confidence: 99%
“…Given the findings of the CPAP studies, there is concern that HFNC may expose infants to noise levels greater than from CPAP. A recent in vitro study17 is the first to compare noise production from HFNC with that from CPAP. Noise levels generated by two HFNC devices (Fisher & Paykel ‘Optiflow’ and Vapotherm ‘Precision Flow’) were higher than those produced by continuous-flow CPAP, and again well above recommended levels.…”
Section: Introductionmentioning
confidence: 99%